Exploring the Association Between Internet Addiction and Upper Cross Syndrome in University Students: A Scoping Review - Aala, Hubtul; Trivedi, Navjyot (Journal of Neonatal Surgery, 2025)
ABSTRACT Background: The increasing prevalence of Internet Addiction (IA) among university students raises critical concerns about its physical health impacts, particularly musculoskeletal disorders such as Upper Cross Syndrome (UCS). Postural abnormalities and muscle imbalances are hallmarks of UCS, which are frequently made worse by extended usage of devices in non-ergonomic postures. Objective: This scoping review's objectives are to provide an overview of the literature on the connection between IA and UCS, point out any gaps, and make recommendations for further study. Methods: Using a systematic review process, Web of Science, PubMed, Scopus, and Google Scholar databases were searched. Studies that focused on university students and subjects pertaining to IA, UCS, or similar musculoskeletal disorders were chosen utilizing strict inclusion criteria. Results: Only one of the 20 pertinent papers that the review found directly examined the connection between IA and UCS and found a significant correlation. Indirect evidence from the remaining trials connected IA to poor posture, extended periods of inactivity, and a higher risk of musculoskeletal pain. The influence of forward head posture, static postures, and psychological stress associated with IA were among the important processes found. Conclusion: The results highlight the critical need for intervention-based and longitudinal research to investigate causal links and successful preventative measures. The review also emphasizes how crucial it is to include programs for physical exercise and ergonomic education in attempts to mitigate the negative effects of IA on physical health. Thorough studies in these fields will provide the door to focused treatments aimed at reducing UCS risks and enhancing college students' quality of life.